Lamiaceae family-derived endophytic fungi: induced tolerance to drought stress in Thymus vulgaris plants - Afsoun Kamyab; Davood Samsampour; Navid Ahmadinasab; Abdonnabi Bagheri (BMC Plant Biology)
Abstract Background Thymus vulgaris is a valuable medicinal plant widely cultivated for its aromatic and medicinal properties. However, like many plants, T. vulgaris faces challenges such as drought stress, which significantly affects its growth, morphological, physiological, and biochemical processes. Understanding how endophytic fungi isolated from Lamiaceae family influence T. vulgaris under varying watering regimes can enhance its resilience against drought stress. This study aims to assess the impact of individual and co-inoculation of three native endophytic species, i.e., Fusarium sp. (F1), Cladosporium puyae (F2), and Curvularia australiensis (F3), on T. vulgaris growth parameters under different irrigation regimes in greenhouse conditions. Results It has been discovered that using fungal endophytes as a biological tool can benefits T. vulgaris under drought stress. The results indicated that drought stress significantly reduced the growth, chlorophyll, and carotenoid content of plants lacking endophytes. Combinatory applications with fungal endophytes significantly improved the above-mentioned parameters under drought stress. Lipid peroxidation levels were significantly reduced in plants inoculated with bacterial endophytes. Drought stress significantly increased the activities of ascorbate peroxidase (APX), superoxide dismutase (SOD), glutathione reductase (GR), peroxidase (POD), and catalase (CAT) in drought conditions. Conclusions The findings suggested that the addition of fungal endophytes to the inoculum enhances drought tolerance in T. vulgaris by mitigating the harmful impact of drought stress on plant growth and physiological functions. The higher activity of antioxidant enzymes and improved redox state of glutathione are responsible for plants’ greater resistance to drought.